Retrospective analysis of cyclosporine A (sandimmun neoral) efficacy and safety in patients with juvenile idiopathic arthritis - S O Salugina; N N Kuzniina (Научно-практическая ревматология, 2004)
Objective. To assess sandimmun neoral (SN) efficacy and safety in pts with juvenile chronic arthritis (JCA). Material and methods. 25 pts (20 girls, 5 boys) aged 3 to 15,5 years (mean 9,7±3,7 years) with JCA were included. 12 from them had systemic and 13 - joint form of the disease. 92% of pts had polyarthritis and 8% - oligoarthritis. Mean duration of the disease was 5,22+2,5 years (1,5-9,5 years). SN dose varied from 0,5 to 5 mg/kg/day (mean 2,9±l,l mg/kg/day). Treatment duration ranged from 1 month to 5 years. Results. Good and fair effect was achieved in 48% of pts. Swollen joint count significantly decreased particularly after a year of treatment. Laboratory indices of inflammatory activity did not decrease significantly. In 52% of children response to the treatment was unsatisfactory or absent. Half of the pts (52%) had adverse reactions during the treatment with SN. Blood creatinine level elevation was the most significant (8 pts). The reason for the treatment termination was absence of the effect in 8, creatinine elevation - in 2 and financial problems - in 5 pts. Conclusion. Treatment with SN was effective in half of the pts particularly in joint form of JCA.In the whole drug tolerability was good, while half of the pts had adverse reactions which usually did not required treatment termination.